Sixty-Four-Row Multisection CT Angiography for Detection and Evaluation of Ruptured Intracranial Aneurysms: Interobserver and Intertechnique Reproducibility - Lubicz, B.; Levivier, M.; François, O.; Thoma, P.; Sadeghi, N.; Collignon, L.; Balériaux, D. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The purpose of this work was to assess intertechnique and interobserver reproducibility of 64-row multisection CT angiography (CTA) used to detect and evaluate intracranial aneurysms.MATERIALS AND METHODS: From October 2005 to November 2006, 54 consecutive patients with nontraumatic subarachnoid hemorrhage (SAH) underwent both CTA and digital substraction angiography (DSA). Four radiologists independently reviewed CT images, and 2 other radiologists reviewed DSA images. Aneurysm diameter (D), neck width (N), and the presence of a branch arising from the sac were assessed.RESULTS: DSA revealed 67 aneurysms in 48 patients and no aneurysm in 6 patients. Mean sensitivity and specificity of CTA for the detection of intracranial aneurysms were, respectively, 94% and 90.2%. For aneurysms less than 3 mm, CTA had a mean sensitivity of 70.4%. Intertechnique and interobserver agreements were good for the detection of aneurysms (mean κ = 0.673 and 0.732, respectively) and for the measurement of their necks (mean κ = 0.753 and 0.779, respectively). Intertechnique and interobserver agreements were excellent for the measurement of aneurysm diameters (mean κ = 0.847 and 0.876, respectively). In addition, CTA was accurate in determining the N/D ratio of aneurysms and adjacent arterial branches. However, the N/D ratio was overestimated by all of the readers at CTA.CONCLUSION: Sixty-four-row multisection CTA is an imaging method with a good interobserver reproducibility and a high sensitivity and specificity for the detection and the morphologic evaluation of ruptured intracranial aneurysms. It may be used as an alternative to DSA as a first-intention imaging technique in patients with SAH.